2007
DOI: 10.1111/j.1600-0609.2007.00987.x
|View full text |Cite
|
Sign up to set email alerts
|

Intervertebral disc calcification in thalassemia intermedia

Abstract: In thalassemia patients, the big variety of spinal deformities may hide the presence of IDC and thus, this entity may be overlooked or underestimated. The clinical significance of IDC development as well as the possible prevention by early transfusion chelation therapy should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Guo et al concluded that serum iron was negatively correlated with the degree of IVDD by a clinical study [ 59 ]. Nevertheless, Aessopos et al suggested that the serum ferritin concentration was not responsible for intervertebral disc calcification in patients with thalassemia intermedia [ 60 ]. Notably, cellular iron homeostasis is important for the normal physiological functions of the body, and both iron overload and deficiency can have disastrous consequences for intervertebral disc cells.…”
Section: Potential Mechanisms Of Ferroptosis In Ivddmentioning
confidence: 99%
“…Guo et al concluded that serum iron was negatively correlated with the degree of IVDD by a clinical study [ 59 ]. Nevertheless, Aessopos et al suggested that the serum ferritin concentration was not responsible for intervertebral disc calcification in patients with thalassemia intermedia [ 60 ]. Notably, cellular iron homeostasis is important for the normal physiological functions of the body, and both iron overload and deficiency can have disastrous consequences for intervertebral disc cells.…”
Section: Potential Mechanisms Of Ferroptosis In Ivddmentioning
confidence: 99%
“…In comparison to age-and sex-matched controls, βTM patients also show statistically significant more severe and extensive degenerative disc disease with no clear mechanism suggested by the literature so far 48 . Its pattern is different exhibiting a multilevel involvement -the whole lumbar spine and several thoracic levels are affected-, intranuclear gas and calcification within discs ( Figure 6) 42,49 .…”
Section: Spinementioning
confidence: 99%
“…They suggested the possibility of early iron chelation therapy in order to prevent complications from IDC. Incidence of IDC in the general adult population is approximately 5–6% and approaches 45% in those over the age of 85 years 6. Presence of IDC in this patient was likely secondary to her underlying condition and not to iron chelation therapy, as treatment was initiated after imaging documentation of two levels of IDC.…”
Section: Discussionmentioning
confidence: 81%
“…Aessopos et al 6 reported intervertebral disc calcification (IDC) in 7 of 30 (23.33%) β-thalassaemia intermedia patients. The patients with IDC had more back pain but otherwise had similar laboratory parameters (of iron excess, extramedullary haematopoiesis, etc) compared to those without IDC.…”
Section: Discussionmentioning
confidence: 99%